Analisis Yuridis Kontradiksi Peraturan Presiden Nomor 20 Tahun 2018 tentang Tenaga Kerja Asing dengan Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan - Julianto Julianto (Universitas Internasional Batam, 2019)
The issuance of Presidential Regulation Number 20 of 2018 concerning the Use of Foreign Workers intended to increase investment has caused controversy in the community, the purpose of this research is to analyze and describe the contradictions that occur with the issuance of Presidential Regulation Number 20 of 2018 concerning the Use of Foreign Workers for Law Number 13 of 2003 concerning Manpower. This research is a normative research, the method used in this study is the collection of secondary data using books, journals, research results, internet searches and related regulations. Government continues to implement the Presidential Regulation with consideration as a step in accelerating the national and regional development process by accelerating the transfer of science and technology and increasing foreign investment to support the national economy and expand employment opportunities through increased investment.